Flexible control of biohythane composition and production by dual cathodes in a bioelectrochemical system. (January 2020) - Li, Xiao; Liu, Guangli; He, Zhen
Graphical abstract: Highlights: Dual-cathode BES accomplishes the production of both hydrogen and methane. Methane production is believed to be via hydrogen conversion by methanogens. The ratio between CH4 and H2 is controlled by adjusting external resistance. High external resistance of H2 -cathode leads to more applicable biohythane. Abstract: Flexible control of CH4 /H2 ratio in biohythane is important to its applications but remains a challenge. Herein, a dual-cathode bioelectrochemical system (BES) was developed for achieving biohythane production with controllable composition through adjusting external resistance. The BES was started as a microbial electrolysis cell to produce hydrogen in both cathodes ("H2 -cathode") and then evolved to produce methane production in one cathode with inoculation of anaerobic sludge ("CH4 -cathode"). When increasing the external resistance of the H2 -cathode from 10 to 330 Ω, its H2 production decreased from 173 ± 11 to 8 ± 2 L m −3 d −1 . This redistribution of electrons has benefited the CH4 -cathode that had an increased CH4 production from 25 ± 3 to 90 ± 5 L m −3 d −1 . The CH4 /H2 ratio increased from 0.14 to 11, making biohythane more applicable to natural gas engines. Those results will help to formulate a BES-based approach to accomplish controllable biohythane production.